Identifikasi Jenis-Jenis Mangrove Di Pantai Ya’ang, Desa Labuhan, Kecamatan Brondong, Kabupaten Lamongan - Raka; Nor Sa’adah; Perdana Ixbal Spanton M; Amir Yarkhasy Yuliardi (Universitas Hang Tuah, 2023)
Brondong District, Lamongan Regency has many types of mangroves in the coastal area and has a coastline reaching 47 km, Lamongan Regency and a mangrove forest area of around 53.37 Ha.This research aims to determine the types and characteristics of mangroves. The method used is explorative survey.The results of the study showed that Brodong District, Lamongan Regency had various types of mangroves as many as 6 types of mangroves consisting of Avicennia marina, Avicennia alba, Rhizophora mucronata Rhizophora stylosa, Bruguiera gymnorrhiza and Sonneratia alba.